Applied econometric analysis emerging research and opportunities - Sloboda, Brian W., 1968-; Sissoko, Yaya, 1961- (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book examines the application of econometric methods as used by researchers in academia, public policy, and areas in social science and business"--